The Role of Common Agricultural Policy for Enhancing the Resilience of Rural Areas under the Current Global Challenges - ANDREEA - EMANUELA DRĂGOI (Global Economic Observer)
Currently the new Common Agricultural Policy (CAP) for the period 2023-2027 proposes a series of development objectives that allow Member States to design their CAP Strategic Plans for enhancing the resilience of rural areas through targeted actions to increase agricultural production and food security, while supporting climate and environmental objectives. This paper aims to identify the concrete ways in which funding granted through the CAP can contribute to increasing the resilience of rural areas under the global current challenges brought by the COVID-19 crisis and by the war that Russia started in Ukraine, by analysing some key factors: CAP’s role for boosting the competitiveness of European agriculture, supporting the growth and employment in rural areas, supporting farm income, financing the environmental objectives and, last but not least, finding solutions to increase food security. For this purpose, the latest statistics on CAP allocations for the two pillars (Pillar I – agriculture and markets and Pillar II – rural development) will be presented, as well as the evolutions of trade in agricultural products and agricultural production at EU-27 level in order to highlight how can CAP respond to the challenges brought by the pandemic, the war in Ukraine and the climate change, while financing the sustainable development of EU’s rural areas and supporting a competitive agriculture in the Member States.